Lidded Jar from Grave No. 40 at Tell El-Murra Cemetery (Studies in Ancient Art and Civilisation, 2021)
The goal of the article is to provide data about a lidded jar discovered in a Tell el-Murra (Nile Delta) grave from the Early Dynastic period. Through the publication of the morphological and technological analysis of the lidded vessel and the details of the place of its discovery, the author would like to make a contribution to the understanding of this kind of jars, known mostly from Upper Egypt and Nubia.